Factors related to medical students’ and doctors’ attitudes towards older patients: a systematic review - Samra, Rajvinder; Cox, Tom; Gordon, Adam L.; Conroy, Simon; Lucassen, Mathijs; Griffiths, Amanda (Oxford University Press, 2017)
Background: Studies have sought to identify the possible determinants of medical students’ and doctors’ attitudes towards older patients by examining relationships with a variety of demographic, educational/training, and job factors. This review collates and synthesises these findings.